Total synthesis of marine natural products serinolamide A and columbamide D - Ghotekar, G. S.; Mujahid, M.; Muthukrishnan, M. (ACS Omega, 2019)
In this report, an expeditious synthesis of two new biologically active marine natural products serinolamide A and columbamide D is documented. This convergent approach involves the key steps such as hydrolytic kinetic resolution, cross metathesis, Grignard reaction, Johnson–Claisen rearrangement, Mitsunobu, and so forth. Both of the target molecules were obtained from a common precursor (R)-7 with high enantioselectivity, less synthetic steps, and in good overall yields (serinolamide A 66% and columbamide D 62%).